PENGARUH PENILAIAN KINERJA, DISIPLIN KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING DI PT. MMS GROUP INDONESIA - Aprilia Kristiani; Lies Putriana; Fahruddin Salim (JURNAL CAFETARIA, 2022)
The purpose of this study was to determine the effect of Performance Appraisal, Work Discipline and Compensation on Employee Performance through Motivation as an intervening variable at PT. MMS Group Indonesia. The sample in this study were 265 employees. The data analysis method used SEM-PLS with Smart PLS 2.0 software. The results showed that the performance appraisal had an effect on motivation, the performance appraisal variable was known to have a significant effect on motivation of 0.309 or 30.9%, while the performance appraisal variable had a significant effect on employee performance of 0.184. The work discipline variable also has a significant effect on employee performance, which is 0.362 or 36.2%. And the compensation variable also has a significant effect on motivation, which is 0.503 or 50.3%. However, the compensation variable on employee performance with 0.166 or 16.6% has no significant effect, while the motivation variable has a significant effect, namely 0.239 or 23.9%. It can be concluded that Work Discipline and Motivation have a significant influence. It can be concluded that Compensation has an indirect effect compared to Work Appraisal and Work Discipline on employee performance through Motivation. The value of R square for the motivation variable is 0.552 or 55.2%. The value of R Square for the employee performance variable obtained is 0.621 or 62.1%. These results show that Performance Assessment, Work Discipline, and Compensation together have an effect of 62.1% on Employee Performance.